Alternative Evidence Using Forensic Science Towards Sodomy and Tribadism Cases in Syariah Court - Muhammad Hazim Ahmad; Ruqayyah Razak; Nurul Syahirah Saharudin; Hendun Abd. Rahman Shah; Hasnizam Hashim; Ahmad Syukran Baharuddin (Usuli Faqih Research Centre PLT, 2024)
Non-Indexed Publication